A content analysis: Consider mindfulness in response to colorist biases. Issue 7 (3rd October 2022) - Ransom, Nicole; Williams, Maya A.; Keyes, Latocia; Hall, Ronald E.
ABSTRACT: Via colorist and white privilege, colorism and racism mirror one another. Colorism is internalized racism; an oppressive internalization regarding phenotypes and skin tones. Mindfulness and other self-reflective practices have been used to modify manifestations of racism such as prejudiced thoughts and biased behaviors. Mindfulness may also help change expressions of colorism as a derivative of racism. Therefore, the implicit manifestations of colorism were further examined in addition to the viability of mindfulness as an intervention. A review of existing literature was conducted using secondary data collection. Analysis resulted in thematic formulation. The findings suggest increasing awareness and self-determination are salient in mindfulness response to colorist bias and behaviors. Mindfulness alone is symbolic of the past and present legacy that African Americans face with embedded racism and colorism experiences. Social workers will find it optimal to use interventions that aid in transforming colorist bias. Implications for healing others from colorism implicit bias is proposed in social workers' use of self-reflective practices and the RAIN modality, illustrative of actions to recognize, allow, investigate, and nurture. Continuous education is vital in social work practice; therefore, future research is suggested to build on this review because colorism as a hierarchy affects all of humanity.